A pregnant woman with uncommon symptoms and complications of covid19: Case report - Nooshin Eshraghi; Maryam Kashanian; Nasim Eshraghi; Niloofar Sarchami; Nahid Nafisi (Mashhad University of Medical Sciences, 2021)
Introduction: The most common signs and symptoms of the novel coronavirus disease which causes severe acute respiratory syndrome include: fever, dry cough, dyspnea and myalgia. But the remarkable point is that half of the patients with this infection have digestive symptoms. In this study, a case of covid-19 with atypical symptoms is reported. Case presentation: A 24-year-old pregnant woman with generalized abdominal pain, bloat and losing appetite without respiratory signs referred to Akbarabadi hospital. Regarding to the epidemic of covid-19 and febrile of the mother after 20 hours, PCR test was done and the result was positive. Emergency appendectomy was done obliquely through a McBurneys point. Pathological results confirmed perforated appendicitis. Conclusion: Since now coronavirus infection is a pandemic, PCR test should be considered for patients with no typical symptoms, but they have acute digestive symptoms; because in the present case with covid-19, appendicitis progressed rapidly and increased maternal morbidity and complications.